THE DESCRIPTION OF CHARACTERS IN LITERATURE (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
American literature is the body of written works produced in the English language in the United States. Like other national literatures, American literature was shaped by the history of the country that produced it. American writing began with the work of English adventurers and colonists in the New World chiefly for the benefit of readers in the mother country.